2018
DOI: 10.4152/pea.201801023
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Corrosion Inhibition Performance Relationship: Application to Some Natural Free Acids and Antioxidants

Abstract: The inhibition of mild steel corrosion in a 1 M HCl solution by some natural free acids and antioxidants has been investigated by weight loss measurement, potentiodynamic polarization and DFT calculations. The experimental results have shown that these compounds exhibited a good corrosion inhibition. The inhibition efficiency increased with the inhibitor concentration. The adsorption of the inhibitor molecules onto the metal surface was found to respond to Langmuir adsorption isotherm for ascorbic, oleic and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…The polarization curves shown in Figure 5 and the values of corrosion parameters shown in Table 3 once again have confirmed the protective effect of carboxylic acids on the corrosion of tin in the 0.5 mol/dm 3 NaCl electrolyte solution. It is also observed that the addition of the tested inhibitors retards both the cathodic and anodic reactions; however, the cathodic reactions are comparatively more affected than the anodic ones, suggesting that the investigated inhibitors are mixed type inhibitors and predominantly act as cathodic inhibitors [24,25]. Other films have also shown high efficiencies, so both deposition methods have shown to be effective for forming films that successfully prevent the corrosion of the tested tin electrode in this electrolyte.…”
Section: Potentiodynamic Polarization Measurementsmentioning
confidence: 84%
See 3 more Smart Citations
“…The polarization curves shown in Figure 5 and the values of corrosion parameters shown in Table 3 once again have confirmed the protective effect of carboxylic acids on the corrosion of tin in the 0.5 mol/dm 3 NaCl electrolyte solution. It is also observed that the addition of the tested inhibitors retards both the cathodic and anodic reactions; however, the cathodic reactions are comparatively more affected than the anodic ones, suggesting that the investigated inhibitors are mixed type inhibitors and predominantly act as cathodic inhibitors [24,25]. Other films have also shown high efficiencies, so both deposition methods have shown to be effective for forming films that successfully prevent the corrosion of the tested tin electrode in this electrolyte.…”
Section: Potentiodynamic Polarization Measurementsmentioning
confidence: 84%
“…where R is the universal gas constant, T is the absolute temperature, T = 298 K, and 55.5 is the concentration of water in the solution in mol dm -3 . The Langmuir adsorption isotherm has been reported for the adsorption of SA on metal surfaces [24]. The adsorption constant and Gibbs free energy were determined to be Kads = 2578 dm 3 mol -1 and Gads = −29.4 kJ mol -1 .…”
Section: Adsorption Isothermmentioning
confidence: 97%
See 2 more Smart Citations
“…It is important to note that some of the organic acids and other chemical compounds present in foods can exert inhibitive effects on the corrosion of certain metals/alloys under acidic conditions consistent with foods such as: citric acid on aluminium in 2 M NaCl solution at pH 2 [ 16 ], ascorbic acid on mild steel in 0.01 M H 2 SO 4 solutions at pH = 2–6 and 0.3% NaCl solution at pH near neutral [ 9 , 17 ], folic acid on mild steel in 0.3% NaCl solution at pH near neutral [ 9 ], vitamins on mild steel in acidic media [ 9 , 17 , 18 , 19 , 20 , 21 ], antioxidant compounds normally present in foods on carbon steel in acidic medium [ 22 , 23 , 24 ], and amino acids on mild steel in acidic solutions [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ]. Some peptides (compounds consisting of two or more amino acids) have been reported to bind strongly to aluminium and mild steel [ 36 , 37 , 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%